The impact of therapy on the risk of asthma in type 2 diabetes. (2nd April 2019) - Rayner, Louise H.; Mcgovern, Andrew; Sherlock, Julian; Gatenby, Piers; Correa, Ana; Creagh‐Brown, Ben; deLusignan, Simon
Abstract: Background and Objectives: There are limited data about the risk of asthma in people with diabetes. We examined the incidence of asthma in subjects with type 2 diabetes (T2DM) compared to controls, and the association with metformin, sulphonylureas and insulin therapy. Materials and Methods: We conducted a retrospective cohort study using a representative UK primary care database ( N = 894 646 adults). We used 1:1 propensity score matching (age, gender, socio‐economic deprivation, body mass index and smoking status) to match 29 217 pairs of T2DM cases and controls. We used Cox proportional hazard regression to compare the incidence of asthma in both groups over 8 years of follow‐up. In those with T2DM, we used Cox proportional hazard regression to assess for any impact of antidiabetic medications on asthma incidence. Results: Individuals with T2DM were less likely to develop asthma than matched controls (hazard ratio [HR] 0.85, 95% CI 0.77‐0.93). Insulin increased the risk of incident asthma (HR 1.25, 95% CI 1.01‐1.56), whilst metformin and sulphonylureas were associated with reduced risk (HR 0.80, 95% CI 0.69‐0.93 and HR 0.76, 95% CI 0.60‐0.97, respectively). There was no association with diabetes duration, complications or glycaemic control. Conclusions: T2DM may have a protective effect against asthma development. Insulin use was associated with an increased risk of asthma, while metformin and sulphonylureas reduced the risk in those with T2DM.